Analysis of the Effects of Carbon Taxes on Sustainable Business Operations - Mutahira Nur Insirat; Nur Sandi Marsuni (GoodWill, 2021)
As global warming becomes an increasingly urgent concern, the implementation of carbon taxes has emerged as a key policy tool to mitigate greenhouse gas emissions. This paper analyzes the effects of carbon taxes on sustainable business operations, focusing on their implications for industry, economy, and social welfare. Through a literature review methodology, it examines the rationale behind carbon taxes, their implementation strategies, and their impact on various sectors, particularly in the context of Indonesia. Carbon taxes are designed to incentivize the reduction of carbon emissions by imposing levies on carbon-based fuels. While they may initially raise concerns about their impact on economic activities, studies have shown that carbon taxes can effectively reduce emissions and foster innovation in renewable energy. Furthermore, revenue generated from carbon taxes can be allocated to important sectors such as education, healthcare, and public transportation, thereby improving social welfare. The paper also discusses the implementation of carbon taxes in Indonesia, highlighting the need for careful consideration to avoid negative impacts on industries and consumers. It explores the potential benefits of carbon tax revenues for the development of renewable energy infrastructure and emphasizes the importance of transparency in tax management to garner public support and ensure accountability. Through a comprehensive analysis of existing literature and empirical evidence, this paper provides insights into the role of carbon taxes in promoting sustainable business practices and addressing climate change challenges. It underscores the importance of policy coherence, stakeholder engagement, and targeted interventions to maximize the benefits of carbon taxation while minimizing adverse effects on the economy and society.